Predictors for raised body temperature in term healthy neonates during the 1st days of life: A teaching hospital study (Indian Journal of Child Health, 2021)
Background: Raised body temperature during the neonatal period is considered an alarming sign of systemic infection. However, infection is not the only cause of a raised body temperature in newborns. Elevations in temperature (>37.5°C) are occasionally noted on the 2nd–3rd day of life in infants who are otherwise healthy and asymptomatic. This disturbance is especially likely to occur in breastfed infants or in infants exposed to high environmental temperatures. Objective: The objective of the study was to find out the important predictors for raised body temperature in full-term infants during the 1st days of life and also the rate of neonatal sepsis among these neonates. Study Design: An observational study was conducted on 50 cases and 50 controls (full-term neonates aged 2–7 days) in a single, tertiary institution in East India over a period of 2 years. Results: Inadequate breastfeeding, weight loss, high birth weight, over clothing, inefficient environmental ventilation, and increased ambient environmental temperature were significantly more common in the study group and hence are the most significant predictors for raised body temperature during the 1st days of life. Out of the 50 babies in the study group, only four had positive sepsis screening. Conclusion: Raised body temperature in asymptomatic full-term breastfed babies during the initial days of life (but after the 1st day) is related primarily to dehydration along with factors such as high birth weight, inefficient environmental ventilation, and ambient environmental temperature. Infection is the least common explanation for raised temperature during that period.